A High-Throughput Screening Assay Using a Photoconvertable Protein for Identifying Inhibitors of Transcription, Translation, or Proteasomal Degradation. (April 2017) - Heidary, David K.; Fox, Ashley; Richards, Chris I.; Glazer, Edith C.
Dysregulated transcription, translation, and protein degradation are common features of cancer cells, regardless of specific genetic profiles. Several clinical anticancer agents take advantage of this characteristic vulnerability and interfere with the processes of transcription and translation or inhibit protein degradation. However, traditional assays that follow the process of protein production and removal require multistep processing and are not easily amenable to high-throughput screening. The use of recombinant fluorescent proteins provides a convenient solution to this problem, and moreover, photoconvertable fluorescent proteins allow for ratiometric detection of both new protein production and removal of existing proteins. Here, the photoconvertable protein Dendra2 is used in the development of in-cell assays of protein production and degradation that are optimized and validated for high-throughput screening. Conversion from the green to red emissive form can be achieved using a high-intensity light-emitting diode array, producing a stable pool of the red fluorescent form of Dendra2. This allows for rates of protein production or removal to be quantified in a plate reader or by fluorescence microscopy, providing a means to measure the potencies of inhibitors that affect these key processes.